Wudu as Islamic Psychotherapy to Improve Sleep Quality in Young Women - Iredho Fani Reza (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Many previous studies have tried to find therapies in dealing with poor sleep quality in women. Where many researchers find that women are more likely to have poor sleep quality than men. Therefore, this study is to prove the effectiveness of wudu as a psychotherapy for sleep quality. This research is a quantitative pre-experimental research with One-Group Pretest-Posttest Design. Research respondents were determined by the purposive sampling technique (N = 17) all of them were young women. To measure sleep quality using the Sleep Quality Scale developed by Yi, Shin, and Shin (2006). Data analysis techniques using the Paired Samples T-Test technique using the help of JASP (Jeffrey's Amazing Statistics Program) version: 0.8.5.1. This study found that wudu therapy is effective in improving sleep quality in young women by focusing on increasing satisfaction with sleep which consists of three indicators namely: 1) Satisfaction Level with overall sleep; 2) Sleep tight; 3) Enough sleep.